Water Retaining Capacity of Some Seeds and Resins - Sivakumar, R.; Umayoru Bhagan, V. (Asian Journal of Chemistry, 2016)
Resins and seeds have the property of absorbing water. Among the studied seeds and resins, viz., Lepidium sativum (A), Hygrophila uriculata (B), Osimum basilicum (C), Azadirachta indica (D), Moringa oleifera (E), Moringa oleifera has been found to have high water absorbing and retaining capacity. Moreover, Moringa oleifera with 2% copper sulphate solution when placed near the roots of the plant, the release of water was slowed down without any fungal attack.